Mining Genomes of Marine Cyanobacteria for Elements of Zinc Homeostasis - Barnett, James P.; Millard, Andrew; Ksibe, Amira; Scanlan, David J.; Schmid, Ralf; Blindauer, Claudia A. (Frontiers in Microbiology, 2012)
Zinc is a recognized essential element for the majority of organisms, and is indispensable for the correct function of hundreds of enzymes and thousands of regulatory proteins. In aquatic photoautotrophs including cyanobacteria, zinc is thought to be required for carbonic anhydrase and alkaline phosphatase, although there is evidence that at least some carbonic anhydrases can be cambialistic, i.e., are able to acquire in vivo and function with different metal cofactors such as Co2+ and Cd2+. Given the global importance of marine phytoplankton, zinc availability in the oceans is likely to have an impact on both carbon and phosphorus cycles. Zinc concentrations in seawater vary over several orders of magnitude, and in the open oceans adopt a nutrient-like profile. Most studies on zinc handling by cyanobacteria have focused on freshwater strains and zinc toxicity; much less information is available on marine strains and zinc limitation. Several systems for zinc homeostasis have been characterized in the freshwater species Synechococcus sp. PCC 7942 and Synechocystis sp. PCC 6803, but little is known about zinc requirements or zinc handling by marine species. Comparative metallo-genomics has begun to explore not only the putative zinc proteome, but also specific protein families predicted to have an involvement in zinc homeostasis, including sensors for excess and limitation (SmtB and its homologs as well as Zur), uptake systems (ZnuABC), putative intracellular zinc chaperones (COG0523) and metallothioneins (BmtA), and efflux pumps (ZiaA and its homologs).